Highway and tourist map of the province of Québec, 1929 - Province of Québec (Producer)
A bilingual tourist map issued by the Province of Québec in 1929. A legend in the lower left corner notes road conditions, international, provincial and county borders, highways, national parks, First Nations reserves, watersheds, aerodromes and customs posts. Local industries are marked in red. An inset map in the lower right shows the Montreal area. A chart in the upper left lists the length of highways and distances between cities in miles. Notes around the map contain various tips for travelers including speed limits and sign symbols. Scale is 1:1,140,480. Material digitized as part of an Academic Innovation Fund (AIF), awarded in 2018. For more information see: http://avptl.info.yorku.ca/academic-innovation-fund/ .